Histomorphological and carbohydrate histochemical study of the pancreas in native ducks (Anas Platyrhynchos) - Saffanah K. Mahmood; Naziha S. Ahmed; Ghada A. Sultan; Mowaffak J. Yousif (Iraqi Journal of Veterinary Sciences, 2022)
In the current study, the histomorphological and histochemical characteristics of the pancreas in native ducks are examined with a particular emphasis on the structure of pancreatic acini and Langerhans islets (LI). Five adult male native ducks (Anas Platyrhynchos) are examined from the local market of Mosul. All samples are processed routinely for histological and histochemical analyses. Hematoxylin & Eosin, PAS-AB (pH 2.5), Toluidine blue, and Masson's Trichrome stains are used. The morphological examination reveals that male ducks’ pancreas is made up of three major lobes (dorsal, ventral, and third lobes). The pancreas is a small, semi-wide structure with a pale to white pinkish tone located between the duodenum branches. The findings show that the pancreas is enveloped in a thin layer of loose connective tissue capsule and mesothelial; septa extend from the capsule into parenchyma dividing it into many lobules. The study concludes that the pancreatic lobules are composed of a large area of exocrine acini and a small amount of LI, with an exocrine component consisting of round or oval acini with zymogen granules. The endocrine component is represented by three distinct LI types and lacks defined boundaries. Alpha islets are formed of alpha cells (ACs) and a few delta cells (DCs); beta islets are composed of peripherally located beta cells (BCs) and a few (DCs); and mixed islets are composed of alpha, beta, and delta cells. The present study sheds light on the morphological, histological, and histochemical characteristics of the indigenous duck pancreas. However, future research should focus on the pancreas of other bird species as well.